PENGARUH PENGETAHUAN KEWIRAUSAHAAN, EFIKASI DIRIDAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA SISWA PADA KELOMPOK BISNIS DAN MANAJEMEN (Survei Pada Siswa Kelas XII di SMK Negeri di Kota Bandung) - Yulvitriyani Br Sebayang (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2018)
This study is based on the lack of student’s entrepreneurial intention at SMK Negeri Bandung thar marked by the number of unemployes are dominated by vocational secondary graduates, especially in Bandung. Theoretically, entrepreneurial intentions is influenced by several factors that derived from within and outside the student. Therefore, the purpose of this study is to determine the influences of Entrepreneurship Knowledge, Self-Efficacy and Family Environment on Entrepreneurial Intention of XII’s grade students in business and Management Group at SMK Negeri Bandung. The population are XII’s grade students in Business and Management Group at SMK Negeri Bandung, sample selection using proportionate random sampling method by collecting 275 students. Data obtained from primary and secondary data through quetionnaires and information from the school. Results showed Entrepreneurship Knowledge (XI), Self Efficacy (X2) and Family Environment (X3) have a positive influence on Entrepreneurial Intention (Y). This means that the higher the entrepreneurship knowledge, self efficacy and family environment, the higher the students entrepreneurial intentions. The implication of this research is all parties are expected to play their role in educational process in terms of growings entrepreneurial intention, particularly students, parents, teachers, school and government show more support and to give facilitation to students and to provide opportunities for entrepreneurship in school and have led to students entrepreneurial intention.